Pengaruh Bauran Pemasaran (Marketing Mix) Terhadap Volume Penjualan Okky Jelly Drink Pada Distributor PT. Sinar Niaga Sejahtera Di Wilayah Banjarmasin - Purwanto Purwanto; Fitriyadi Fitriyadi; Hasanur Arifin (Universitas Lambung Mangkurat, 2016)
This study was aimed to discover (1) the influence of simultaneous marketing mix on the sales volume of Okky Jelly Drink in Banjarmasin area. (2) the influence of simultaneous marketing mix on the sales volume of Okky Jelly Drink in Banjarmasin area, and (3) to discover the most dominant marketing mix in increasing the sales volume of Okky Jelly Drink in Banjarmasin area. The analysis method used was multiple regression analysis, F test, t test and determination coefficient (R2). Based on research results, it’s concluded that marketing mix had partial positive influence on the sales volume of Okky Jelly Drink in Banjarmasin area. First, it’s proven that products (X1) influenced the sales volume (Y), Second, it’s proven that price (X2) influenced sales volume (Y), Third, it’s proven that distribution channel mix (X3) influenced sales volume (Y) and, Fourth, it’s proven that promotion mix (X4) influenced sales volume (Y). Analysis also concluded that there was influence of simultaneous marketing mix on the sales volume of Okky Jelly Drink in Banjarmasin area. Keywords: Marketing Management, Marketing Mix, Sales Volume